2020
DOI: 10.1038/s41419-019-2201-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic priming by Dot1l in lymphatic endothelial progenitors ensures normal lymphatic development and function

Abstract: Proper functioning of the lymphatic system is required for normal immune responses, fluid balance, and lipid reabsorption. Multiple regulatory mechanisms are employed to ensure the correct formation and function of lymphatic vessels; however, the epigenetic modulators and mechanisms involved in this process are poorly understood. Here, we assess the regulatory role of mouse Dot1l, a histone H3 lysine (K) 79 (H3K79) methyltransferase, in lymphatic formation. Genetic ablation of Dot1l in Tie2(+) endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 72 publications
0
24
0
Order By: Relevance
“…These intriguing findings do not only propose a new scenario in which HDACs can also promote transcription but also that LECs are able to employ enhancer-specific epigenetic signatures to drive appropriate transcriptional programs (Figure 4C). With regard to histone methyltransferases, a very recent study has found a role of DOT1L (DOT1-like histone lysine methyltransferase) during mouse lymphatic vessel development and valve morphogenesis (Yoo et al, 2020). Dot1l knockout mice displayed lymphatic hypoplasia, edema, and underdevelopment of lymphatic valves.…”
Section: Changing Chromatin Profiles To Fine-tune Lec Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…These intriguing findings do not only propose a new scenario in which HDACs can also promote transcription but also that LECs are able to employ enhancer-specific epigenetic signatures to drive appropriate transcriptional programs (Figure 4C). With regard to histone methyltransferases, a very recent study has found a role of DOT1L (DOT1-like histone lysine methyltransferase) during mouse lymphatic vessel development and valve morphogenesis (Yoo et al, 2020). Dot1l knockout mice displayed lymphatic hypoplasia, edema, and underdevelopment of lymphatic valves.…”
Section: Changing Chromatin Profiles To Fine-tune Lec Gene Expressionmentioning
confidence: 99%
“…In particular, DOT1L binds to essential lymphatic genes, such as Sox18, Foxc2, and vegfr3, and drives chromatin opening resulting in their transcriptional activation (Figures 3C and 4C). Interestingly, DOT1L also participates in mesenteric lymphvasculogenesis (Stanczuk et al, 2015) by activating lymphatic genes in the hemogenic endothelial cell population, suggesting a role for DOT1L in the establishment of LEC fate from a non-venous origin source (Yoo et al, 2020).…”
Section: Changing Chromatin Profiles To Fine-tune Lec Gene Expressionmentioning
confidence: 99%
“…The less differentiated hematopoietic progenitors in the yolk sac are unaffected by DOT1L-KO. Vessel disorganization also occurs in the fetal brain at 10.5 upon DOT1L-KO in endothelial cells demonstrating that DOT1L is important for development beyond the extra-embryonic tissue ( Yoo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 23 The NLRP3 inflammasome serves as an intracellular inflammatory machinery, which can be activated by HG condition. 24 Due to the lack of caspase recruitment domain, NLRP3 needs to be combined with ASC to recruit pro caspase1 and cut into mature caspase1 to participate in the release of inflammatory factors. 25 , 26 In the present study, the protective effect and the underlying mechanism of MG IIIE on podocytes treated with HG were studied in vivo to investigate the pathogenesis of DN and the possible novel therapies for it.…”
Section: Discussionmentioning
confidence: 99%